Weather dependence of medical rehabilitation efficiency in patients with ischemic heart disease on the resort of the South Coast of Crimea - A. S. Ivaschenko; V. V. Ezhov; L. V. Yezhova; T. S. Yanovskiy; V. I. Mizin; A. M. Yarosh; P. E. Grigoriev; A. F. Pyankov (Евразийский Кардиологический Журнал, 2021)
The aim of this work is to assess the influence of the climatic and weather characteristics of the South Coast of Crimea (SCC) on the effectiveness of health resort medical rehabilitation (MR) of patients with ischemic heart disease (IHD).Materials and methods. A study was carried out in a group of 276 patients with IHD. The influence of climatic and weather characteristics of the SCC were assessed using the methods developed by the «ARI n.a. I.M. Sechenov» - modified clinical index on weather pathogenicity (CIPP-M) and MR assessment according to the criteria of the» International classification of functioning, disabilities and health» (ICF).Results. Regression equations for the dynamics of the ICF b2401, b280, b4301 and b440 domains on the values of air temperature (AT-M), atmospheric pressure variability (APV), air temperature variability (ATV-M) wind speed (WS-M) and total CIPP-M have been developed, which allow to reliably form a rehabilitation prognosis for patients with IHD for all terms of health resort treatment in the SCC.Conclusions. The use of modernized clinical indices of weather pathogenicity allows one to adequately assess and predict the effect of weather dynamics and form a rehabilitation prognosis for patients with IHD.